2008
DOI: 10.1007/s00192-008-0591-1
|View full text |Cite
|
Sign up to set email alerts
|

Family history as a risk factor for pelvic organ prolapse

Abstract: The aim of this study was to determine whether a family history of prolapse and/or hernia is a risk factor for prolapse. A cohort of 458 women seeking gynecological care was classified as exposed (family history) or unexposed (without family history). We used chi2 to assess confounding and logistic regression to determine risk. Nearly half (47.3%) of the 458 participants reported a positive family history. Of these, 52.5% had prolapse. This was significantly higher than the 28.9% rate of prolapse in women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 21 publications
2
22
0
3
Order By: Relevance
“…Other human studies have suggested that alterations in genes responsible for elastic fiber homeostasis are more common in women with clinical manifestations of POP (23), and family history is a known risk factor for the development of this disease (24). It would be important to understand how genetic susceptibility plays into the elastinopathic pathways identified in murine models.…”
Section: Discussionmentioning
confidence: 99%
“…Other human studies have suggested that alterations in genes responsible for elastic fiber homeostasis are more common in women with clinical manifestations of POP (23), and family history is a known risk factor for the development of this disease (24). It would be important to understand how genetic susceptibility plays into the elastinopathic pathways identified in murine models.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the factors that play a role in the occurrence of pelvic organ prolapse in the first place are also risk factors for recurrence of prolapse after surgery. Risk factors for pelvic organ prolapse that have been described in literature are aging [4, 5], obesity [4, 6], family history of prolapse [7, 8], and collagen weakness [5]. Furthermore, there is a strong relationship between vaginal child birth and pelvic organ prolapse [4, 7, 9].…”
Section: Introductionmentioning
confidence: 99%
“…1 The aetiology of POP is considered to be multifactorial. Based on the recently published integrated life span model, 6 it can be assumed that the development of POP includes predisposing factors (growth and development, genetic factors, connective tissue weakness, joint mobility), [7][8][9][10][11][12] inciting factors (childbirth, pelvic surgery) [12][13][14][15][16][17][18] and intervening factors (age-related changes, obesity, constipation, heavy occupational work, vigorous physical activity). 12,[14][15][16][17][18][19][20][21][22][23][24] Unfortunately, only a minority of these risk factors can easily be prevented.…”
Section: Introductionmentioning
confidence: 99%